Pengaruh Konseling Kelompok Teknik Scaling terhadap Pengambilan Keputusan Karir - Widiyanti, Putri (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
This research is based on the fact that many vocational school students are confused in determining career choices for their future. There are students who have not understood and planned carefully regarding the career path to be taken, both to continue education and work. Some students tend to follow the decisions of their parents or friends without considering their own interests and abilities. The purpose of this study is to determine the effect of the use of scaling techniques in group counseling services on improving students' career decision-making skills. Methods used in literature studies. The results of the study show that group counseling services with scaling techniques are proven to be effective in improving the career decision-making ability of vocational school students. Through scaling techniques, students can identify their current position on the career decision-making scale, as well as determine the concrete steps to take to achieve their expected career goals. The improvement of students' career decision-making skills is inseparable from the process of providing assistance in the form of group counseling with scaling techniques carried out.